1965
DOI: 10.1111/j.1365-2621.1965.tb01877.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles from Grapes I. Some Volatiles from Concord Essence

Abstract: SUMMARY Concord grape essence was examined by GLC‐mass spectrometry and sixteen volatile components identified. Aside from ethyl acetate and ethanol, the most abundant was 2‐methyl‐3‐buten‐2‐ol. Preliminary information on several other components has been obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

1967
1967
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 4 publications
0
9
1
Order By: Relevance
“…Ethyl acetate (peak 6) is the largest component in the grape oil extract. The preponderance of this ester was previously reported (Stevens et al, 1965) but in contrast to the prior investigation only a small amount of 2-methvl-3-buten-2-ol (peak 7) was found. A number of possibilities Hex-2-en-l-ol Webb and Kepner, 1957. b Indicates no retention data.…”
Section: Resultscontrasting
confidence: 59%
See 2 more Smart Citations
“…Ethyl acetate (peak 6) is the largest component in the grape oil extract. The preponderance of this ester was previously reported (Stevens et al, 1965) but in contrast to the prior investigation only a small amount of 2-methvl-3-buten-2-ol (peak 7) was found. A number of possibilities Hex-2-en-l-ol Webb and Kepner, 1957. b Indicates no retention data.…”
Section: Resultscontrasting
confidence: 59%
“…The extensive use of Concord grape (Vitis labrusca) products in the food industry has prompted an investigation of the volatile constituents in the essence. The present communication is an extension of previous work on Concord grape volatiles in which 16 constituents were identified (Stevens et al, 1965). These components along with those identified by Holley et al (1955) are summarized in Table I.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Several methods exist for the determination of MA, including steam distillation followed by fluorescence analysis (Mattick et al, 1963;Casimir et al, 1976;Moyer and Mattick, 1976;Moyer et al, 1977;Reynolds et al, 1982;Liu and Gallander, 1985;Fischer et al, 19901, spectrophotometry (Ekanayake et al, 19901, gas chromatography (Brunelle et al, 1965;Neudoerffer et al, 1965;Stevens et al, 1965;Stern et al, 1967;Nelson et al, 1976;Nelson et al, 1977;Tomlinson and Boison, 19871, and liquid chromatography with W (Schmitt et al, 1986;Viiias et al, 1992;Clark et al, 1993) or (Williams and Slavin, 1977;Viiias et al, 1993) fluores-' Analytical Chemistry Project.…”
Section: Introductionmentioning
confidence: 98%
“…The viniferas, in general however, are characterized by having mild aromas which are not too readily differentiated from one another. Power et al (1921), Holley et al (1955)) Neudoerffer et al (1965), and Stevens et al (1965) have studied the aroma materials of the Vitis labnlsca variety Concord; the first mentioned investigators established the importance of methyl anthranilate to the aroma of the labruscas. Kepner et al (1956) identified a number of volatile aroma substances in J'itis rotzlndifolia and Cordonnier (1956), Webb et al (1957), Stevens et al (1966, Wenzel (1966), and Webb et al (1966), have all investigated the volatile aroma components of the muscats.…”
Section: Introductionmentioning
confidence: 99%